1998
DOI: 10.4141/a98-032
|View full text |Cite
|
Sign up to set email alerts
|

Bunk attendance of feedlot cattle monitored with radio frequency technology

Abstract: . Bunk attendance of feedlot cattle monitored with radio frequency technology. Can. J. Anim. Sci. 78: 707-710. Bunk attendance of 72 feedlot cattle (412 ± 23.6 kg) was monitored for 86 d using radio frequency technology. Late morning and late afternoon were confirmed as primary ad libitum feeding periods. The system detected differences (P < 0.005) in feeding behaviour in response to level of feeding and frequency of meals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 5 publications
2
35
1
1
Order By: Relevance
“…A bedded area was provided away from the bunk, and fresh water was continuously available. Four pens in each trial were equipped with an electronic feed-bunk monitoring system (GrowSafe Systems Ltd., Airdrie, AB) described previously (Gibb et al 1998;Schwartzkopf-Genswein et al 1999). This system recorded animal feeding behaviour but did not record individual animal feed intake.…”
Section: Animals and Housingmentioning
confidence: 99%
“…A bedded area was provided away from the bunk, and fresh water was continuously available. Four pens in each trial were equipped with an electronic feed-bunk monitoring system (GrowSafe Systems Ltd., Airdrie, AB) described previously (Gibb et al 1998;Schwartzkopf-Genswein et al 1999). This system recorded animal feeding behaviour but did not record individual animal feed intake.…”
Section: Animals and Housingmentioning
confidence: 99%
“…Modern transmitters are small and versatile, which has allowed the tracking of many small animals like mice, birds and ghost crabs (Mech 1983). Gibb et al (1998) have monitored bunk attendance of feedlot cattle. Location fixes and accuracy depend on mobile researcher (ground or air), terrain, visibility, discomfort, and fatigue.…”
Section: Vhf Radio Signal Trackingmentioning
confidence: 99%
“…Less-variable TDA during LF1/d than AF1/d supports the theory commonly held by feedlot operators and nutritionists that the consistent feed deliveries carried out during limit feeding and/or clean bunk management protocols equates to increased consistency in intakes by individuals in the pen. Gibb et al (1998) reported that TDA variability with once daily feed delivery was higher during limit feeding than when cattle had ad libitum access to feed. In that study, however, variation was calculated as the average variation from day to day, as opposed to the average daily deviation from the mean duration, which was used to calculate variation in the present report.…”
Section: Trialmentioning
confidence: 99%